Fungsi Manajemen POAC pada Literasi Kopi UPT Perpustakaan Proklamator Bung Karno - Purwanto, Hery; Arisyahidin, Arisyahidin (Otonomi, 2025)
The library is not only a center of information resources but also a place for self-transformation into a socio-cultural hub by empowering and democratizing the community and local populations in an effort to improve public welfare. "Coffee Literacy" is one of the social inclusion programs of the UPT Proklamator Bung Karno Library, conducted in the form of a three-day workshop. It includes theoretical and practical materials about barista skills, attended by participants from the Greater Blitar area who are either already involved in or interested in learning about the coffee industry business. This qualitative research, using a case study strategy, was carried out through data collection methods such as interviews, observation, and focused group discussions to analyze the POAC (Planning, Organizing, Actuating, Controlling) management and to identify challenges and find solutions to optimize the management of the Coffee Literacy program. The results of the study show that the POAC analysis of the Coffee Literacy program indicates: Planning: The concept and technical implementation of Coffee Literacy has been partially achieved, and fully achieved in terms of the objectives, location, timing, and actors involved in the program. Organizing: The planning and development to achieve the program’s goals have not yet been achieved. Resource allocation has been partially achieved, while task delegation and assigning responsibilities have been accomplished. Actuating: Two indicators — staffing and motivating — have not yet been achieved. Controlling: This consists of four indicators — setting implementation standards, determining performance metrics, measuring actual performance and comparing it with standards, and taking corrective actions when deviations occur — none of which have been achieved. From year to year, Coffee Literacy has met the targets set by the Social Inclusion Team of UPT Proklamator Bung Karno Library, which are still limited to participant quotas and have not referred to specific goals and measurable performance indicators (Key Performance Indicators/ KPIs). This has led to several implementation complaints, including technical issues such as delays in the event schedule, diverse levels of participants’ knowledge about coffee, and a mismatch between practice equipment and the large number of participants. It also results in content being perceived as less relevant to current issues in the coffee industry, presentations considered monotonous, and the absence of practical modules that can serve as guides for running a business in the coffee industry